Identifying and Addressing Typographical Errors in Arabic Textbook for Madrasah Ibtidaiyah Students - Tamam, Muhammad Ibnu; Hilmi, Danial; Fitra, Muh. Naufal; Nur, Muhammad Fahrudin (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2024)
Typographical errors in textbooks can affect students' understanding and mastery of Arabic and highlight broader issues in quality control of educational materials for Madrasah Ibtidaiyah. For instance, the Arabic textbook al-Lughah al-'Arabiyyah for sixth grade contains numerous typographical and linguistic errors, potentially hindering the learning process. This study aims to identify and analyze typographical errors in the textbook, which was developed by the Curriculum, Facilities, Institutional, and Student Affairs (KSKK) team of the Indonesian Ministry of Religious Affairs. This research employs a descriptive qualitative method with a literature review approach and content analysis techniques. The findings reveal 28 typographical errors distributed across the material content, practice exercises, and vocabulary sections. These errors are categorized into morphology, syntax, and writing errors (kitabah). Most typographical errors involve incorrect writing of letters or diacritical marks (harakat), which may alter meanings and therefore require correction. This study underscores the importance of enhancing quality control processes in textbook development, particularly in editing and proofreading stages before publication. The findings serve as a reference for publishers to rectify errors in future editions, thereby improving the effectiveness of Arabic language learning in Madrasah Ibtidaiyah.